Occupational Health Hazards and Injuries among Fish Smokers in the Gambia Fishing Communities - Uyamadu, Evelyn Anuli; Sridhar, Mynepali; Ana, Godson; Morakinyo, Oyewale (Discoveries in Agriculture and Food Sciences, 2023)
Fish smoking has now spread throughout the world and is now a highly common method of preserving fish. The Occupational Health Hazards and injuries among fish smokers in the Gambia fishing communities was investigated. Simple random sampling technique was used in the selection of 52 fish smokers from the two study communities. Focus group discussion and interviewer-administered questionnaires were used to collect data on the various hazards and injuries common among them. Data were analyzed using the Statistical Packagefor Social Sciences (SPSS 20.0). Descriptive statistics were used to summarize the data. An analytical statistic test was used to test for association using the chi-square at a 95% significant level.The majority of the fish smokers are married and within the age range of 31-48years.The physical hazards reported were minor cuts(51.2% and 88.9%); fish bites (72.1% and 77.8%); fish stings(75.9% and 66.7%); heat and cold(58.1% and 100.0%); minor head injury(72.1% and 88.9%). For biological hazards, 67.4% and 66.7% reported parasitic infections, 100.0%, and 100.0% reported smoke from the smokehouse as the main chemical hazard. Several, 72.1% and 88.9% reported internal injuries as their major ergonomic hazard. Common perceived injuries sustained during fish smoking among Tanji and Banjul fish smokers were cuts and lacerations (91.1% and 100%); bruises (82.2% and 77.8%); muscle strains and pains(86.7% and 88.9%); sting from fish spines( 71.1% and 100%) and puncture wounds (57.8% and 88.9%). The mean CO of the outdoor fish smoking Environment in Tanji and Banjul were 381.0±154.4 and 436.0±266.8. The mean Indoor CO value in Tanji was 390±350.9. However, in Banjul the mean value was zero. Comparison of the mean outdoor CO values of fish smoking environment in Tanji and Banjul revealed no significant difference (P=0.60) . However, a comparison of mean indoor CO levels for the fish smoking environment in Tanji and Banjul was significantly different (P<0.001).Therefore, it is recommended that all fish smokers receive thorough training on the dangers and risks specific to their line of work and the need to practice safety.